Effects of management of plastic and straw mulching management on crop yield and soil salinity in saline-alkaline soils of China: A meta-analysis - Ying Song; Jineng Sun; Mingjun Cai; Jinyu Li; Meizhen Bi; Mingxiu Gao (Agricultural Water Management)
Improving saline-alkali soils is crucial for sustainable agricultural development. Ground cover techniques, such as mulching, can mitigate soil salinity, but their effects on crop yields and soil salinity remains controversial. Moreover, it remains unclear how these effects vary with climatic, edaphic, and agronomic management factors such as tillage methods, irrigation types, nitrogen application rates, and mulching duration. To address this gap, we conducted a meta-analysis to assess the effects of plastic film mulch (PM), straw mulch (SM), and their combination (SM+PM) on crop yields and soil salinity. Results showed that PM, SM, and SM+PM increased crop yields by 33.7 %, 45.2 %, and 14.5 %, respectively, while reducing soil salinity by 13.9 %, 22.6 %, and 12.7 % compared to no mulch. These improvements were influenced by climate, edaphic, and agronomic factors. Different cover measures significantly increased crop yield and reduced soil salinity under varying mean annual temperature and mean annual precipitation < 300 mm conditions. Regarding soil conditions, PM and SM+PM did not significantly reduce soil salinity under conditions of clay, SBD (soil bulk density) < 1.45 g·cm-³ , SBD > 1.55 g·cm-³ , mild soil salinization, and saline soils. Regarding agronomic practices, PM showed the greater yield improvements under no-tillage, rotary tillage, and deep tillage systems, while SM effectively reduced soil salinity. Notably, the impact of these mulching practices on both crop yield and soil salinity became insignificant when the experimental duration exceeded 2 years. For optimal results, black plastic mulch should be used to cover the entire ground surface when employing PM, while SM should be applied as surface mulch. This research provides valuable insights for selecting appropriate mulching strategies to improve saline-alkali soils and promote sustainable agricultural practices.